Trees, large wood and streams: Using archive survey data to inform changing interactions in a human‐impacted landscape. Issue 14 (1st August 2022) - Gurnell, Angela M.; Hill, Christopher T.; Davis, Richard J.; Tooth, Stephen
Abstract: Monitoring is the key to understanding fluvial systems and a crucial foundation for assessing the outcomes of river restoration. The New Forest, southern England, was designated a National Park in 2005 in recognition of its highly valued landscape, which has been both positively and negatively impacted by over 1000 years of human management. Here we analyse archive field maps and tabulations extracted from walkover surveys that record the distribution and character of wood jams along 59 km of New Forest streams in 1991. By integrating the 1991 archive survey data with other historical information, we analyse associations among stream channel characteristics, wood jams, riparian land cover, and stream and land management at that time. We reveal associations among these factors that reflect the imprint of centuries of grazing, forestry and stream management practices. Along 10 km of one stream (the Highland Water), we analyse data collected during additional walkover surveys in 1997 and 2021, to track changes since 1991. We illustrate how a reduction in stream and wood management over recent decades and the restoration of some stream reaches in 2005 has resulted in overall increases in stream sinuosity and the number of wood jams. The walkover surveys on which our results are based provide an approach to characterizing the impacts of river corridor management in the New Forest landscape that are both cost and time effective and could be applied by non‐specialist volunteers ('citizen scientists') following appropriate training. Survey data of the spatial coverage achieved in 1991 are rare but need to be encouraged in the New Forest and farther afield to provide a robust framework into which more local, specialist surveys can be integrated, and from which the broad impacts of river corridor management approaches can be monitored. Abstract : Through an analysis of data extracted from field maps and tabulations generated from straightforward, rapid, walkover surveys of 59 km streams located in the New Forest (southern England) in 1991 and resurveys of 10 km of these streams in 1997 and 2021, we reveal associations among stream channel dimensions, wood jams, riparian land cover, and stream and land management, that reflect the imprint of over 1000 years of grazing, forestry and stream management.